Co-Occurring Alterations of ERBB2 Exon 20 Insertion in Non-Small Cell Lung Cancer (NSCLC) and the Potential Indicator of Response to Afatinib - Yuan, Bo; Zhao, Jun; Zhou, Chengzhi; Wang, Xiumei; Zhu, Bo; Zhuo, Minglei; Dong, Xilin; Feng, Jiemei; Yi, Cuihua; Yang, Yunpeng; Zhang, Hua; Zhou, Wangyan; et al. (Frontiers in Oncology, 2020)
Background: Human epidermal growth factor receptor 2 (ERBB2, HER-2) exon 20 insertion (ERBB2ex20ins) remains a refractory oncogenic driver in lung cancer. So far there is limited data showing the co-occurring mutation background of ERBB2ex20ins in Chinese lung cancer and its relationship with response to afatinib. Patients and Methods: A total of 112 Chinese patients with ERBB2ex20ins identifiedby next-generation sequencing from 17 hospitals were enrolled. The clinical outcomes of 18 patients receiving afatinib treatment were collected. Results: Among the 112 patients, insertion-site subtypes comprised of A775ins (71%; 79/112), G776indel (17%; 19/112) and P780ins (12%; 14/112). There were 66.1% (74/112) of patients carrying TP53 co-mutation and FOXA1 was the most prevalent co-amplified gene (5.5%, 3/55). The co-occurring genomic feature was similar among three insertional-site subtypes and had an overall strong concordance with the western population from the MSKCC cohort (R2=0.74, P<0.01). For the prognosis, patients with co-occurring mutation in cell-cycle pathway especially TP53 showed shorter OS than patients without [median OS: 14.5m (95%CI:12.7m-16.3m) vs 30.3m (95% CI: not reached), p=0.04], while the OS was comparable among three subtypes. For the response to afatinib, ERBB2ex20ins as a subclonal variant was an independent factor relating to shorter PFS [median PFS: 1.2m (95%CI: 0.8-1.6m) vs 4.3m (95%CI: 3.3m-5.3m), p<0.05]. Conclusion: Our data revealed co-occurring TP53 represent an unfavorable prognosis of patients with ERBB2ex20ins, emphasizing the more valuable role of the co-mutation patterns than insertion-site subtypes in predicting prognosis of this group of patients. Moreover, the clonality status of ERBB2ex20ins was identified as a potential indicator for response to afatinib.